Strength and ductility of RC beams strengthened with ultra high strength cementitious composite overlay - Upreti, Ghanashyam; Murthy, A. Ramachandra; Gopinath, Smitha; Iyer, Nagesh R.; Venkat, L. (Journal of Structural Engineering, 2024)
Strength and ductility are the two important parameters for the design of concrete structures to prevent sudden collapse and minimize damage. An experimental investigation was carried out on pre-damaged RC beams strengthened with Ultra High Strength Cementitious Composite (UHSCC) overlay under four point bending. The aim of the present investigation is to evaluate the strength and ductility of the pre-damaged strengthened RC beams with UHSCC overlay. The enhanced strength after strengthening, ductility using deflection and energy based approach, failure modes and load deflection behavior are discussed. It is observed from the experimental findings that UHSCC overlay significantly enhances the load carrying capacity and ductility. Further, it is noted that both deflection ductility and energy based ductility are in good agreement with each other in the present study.